Efficiency of Use of Labor Resources in Construction Enterprises - Shavkatovna, Komilova Mukammal; o’g’li, Isrofilov Firdavs Ibroxim (Research Parks Publishers, 2023)
This article is dedicated to the sufficient supply of necessary labor resources of construction enterprises in our Republic, their rational use and increase of production efficiency. Also, the scientific conclusions developed by the authors on increasing the potential of labor resources in the near future are described.